Expression of Oryza sativa galactinol synthase gene in maize (Zea may L.) - Hoi, Pham Xuan; Hue, Huynh Thi Thu; Hang, Pham Thu; Phuong, Nguyen Duy (Academia Journal of Biology, 2019)
Galactinol synthase (GolS) is a key biological catalyst for the synthesis of the raffinose oligosaccharides (RFOs) which play important roles in abiotic stress adaptation of plants, especially drought tolerance. GolS gene has been isolated on a variety of plants in order to create material resources for generating transgenic plants resistant to adverse environmental factors. In our previous research, we have isolated a GolS gene from drought stress cDNA library of Oryza sativa L. Moctuyen (named OsGolS). In this study, the expression vector pCAM-Rd/OsGolS carrying the isolated OsGolS gene under the control of stress-inducible Rd29A promoter was constructed and introduced into Agrobacterium tumefaciens LBA4404, which was used for maize transformation.  PCR and Real-time PCR assay indicated that transgene was integrated in the genome of the regenerated Zea mays plants. Reverse transcription-PCR showed that the OsGolS was transcribed into mRNA in Zea mays and was highly expressed. These results provide a basis for the study of the function of OsGolS in drought responses and for the development of drought stress tolerant crops.